How do online users perceive health risks during public health emergencies? Empirical evidence from China - Huang, Shijing; Zhou, Cheng; Yuan, Qinjian; Chen, Guohua; Shen, Hongzhou (Frontiers in Psychology, 2023)
The global COVID-19 pandemic has posed a major threat to human life and health, and new media technologies have intensified the spread of risk perception. This study aimed to explore the impact of risk information ground on online users’ perceived health risks, and further explore the mediating role of psychological distance and the moderating role of self-efficacy. A total of 25 Internet users from different provinces in China were interviewed in-depth, risk information ground factors were fully identified, and a unified theoretical model was constructed based on Grounded theory. A total of 492 interviewees were recruited to complete a scenario questionnaire through an online snowball technique. The structural equation model (SEM) of the partial least squares (PLS) method was used to test the conceptual model. And the results showed that information ground factors significantly affected online users’ perceptions of health risks, psychological distance mediated the effect of information ground factors on risk perception, and self-efficacy negatively regulated the effect of psychological distance on risk perception. The results of this study imply that public health administrators should pay attention to the role of psychological distance and self-efficacy in the formation of online users’ health risk perceptions, and also provide a reference for the prevention of and intervention in risk transmission.